Determination of Urinary Neurochemical Biomarkers for Brain Doping Diagnosis through Clinical Study - CHO, YOESEPH; Hana, Park; HEO SOOHYUN; Yoon, Sang Sun; SON, Jung hyun (The 70th Biannual Conference of The Korean Society of Analytical Sciences, 2023)
Brain doping is a novel type of doping that stimulates specific brain regions to improve sports performance; however, there is no definite regulation or detection method to deal with it. We have continued our research to establish a brain doping diagnosis based on the concept that neurochemicals mediate brain stimulation to improve sports performance. In this study, a clinical study was conducted that focused on the effects of transcranial direct current stimulation and tested whether receiving stimulation prior to exercise enhanced sports performance and produced neurochemical alterations. Fifteen subjects participated in a single-blind crossover test to measure the electroencephalogram and sports performance induced by primary motor cortex stimulation. In order to identify changes in neurochemicals, urine was collected at a certain time point from participants and analyzed using an ultra-sensitive analysis method developed in a previous study. Compared to sham conditions, brain stimulation led to changes in movement-related cortical potentials and increases in sports performance. As a result of analyzing the urine of the subjects, the stimulus-dependent change patterns of neurochemicals were confirmed by statistical analysis, and 10 substance-to-substance ratios were suggested as diagnostic criteria for brain doping. In this study, by detecting a whole shift in patterns for neurochemicals, we carried out research to establish a diagnosis strategy for brain doping for the first time. We have identified changes in neurochemicals caused by brain stimulation and secured basic data for neural network research. In addition, the analysis method developed in this research is effective for the simultaneous measurement of neurochemicals in biological samples and is anticipated to be applicable in several sectors, including doping control.